A system analysis tool for sustainable biomass utilisation considering the Emissions-Cost Nexus. (15th April 2020) - Fan, Yee Van; Tan, Raymond R.; Klemeš, Jiří Jaromír
Highlights: Develops a graphical method based on break-even concept to determine the sustainable use of biomass. Compares the emission-cost nexus performance of pyrolysis. Identifies the impact of GHG pricing and carbon emission intensity. Assesses the role of demand increment on the avoided emission accounting. Considers the secondary effect of biochar on soil. Abstract: There is a wide array of biomass utilisation pathways to mitigate greenhouse gas emissions. The characteristic of biomass, the demand for products, and the local constraints determine the sustainability of utilisation. Generic principles and criteria can be applied to the analysis of specific instances. This work develops a decision-making tool for determining the most sustainable use of biomass for carbon management. The mathematical principles are based on break-even analysis and are visualised in the form of a graphical display for transparent communication of results to decision-makers. An essential feature of this tool is that it allows the Emissions-Cost Nexus to be considered in identifying the most sustainable biomass utilisation pathway under different baseline conditions. Economic instruments such as carbon emissions tax can also be determined and calibrated to direct decisions to specific pathways. The use of this tool is illustrated with a case study considering the pyrolysis of two different sources of biomass (residual biomass and energy crop) and plastic waste. Pyrolysis optimised for energy production is generally preferable unless biochar produced is at the quality for soil amendment. However, the change in baseline conditions, e.g. energy demand or carbon emission intensity, could overturn the initially selected utilisation. This result highlights the importance of a better standard to define avoided emissions for appropriate decision making. The case study also suggested that corn stover optimised for energy has a better emission-cost performance than optimised for biochar and carbon sequestration, unless the multiplier effect of biochar application to soil is higher than 1.4. The presented study shows the applicability of the developed method as a useful tool for sustainable biomass and product utilisation.